2022
DOI: 10.1142/s0218625x22501037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Energy Consumption, Cutting Force, Surface Roughness and Vibration in Machining Toolox 44 Steel Using Taguchi-Based Gray Relational Analysis

Abstract: This paper presents the Toolox 44 steel’s experimental and statistical machinability optimizations conducted for achieving minimum output parameters (energy consumption ([Formula: see text]), cutting force ([Formula: see text]), surface roughness ([Formula: see text]), and vibration (Vib)). Turning experiments have been performed under dry machining conditions on a CNC lathe at different cutting parameters according to the Taguchi L27 orthogonal array. Taguchi-based gray relational analysis (GRA) has also been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The symbols N, Tdof, F α,1ƒe , α, ƒe, Ve, R and n eff represents the total number of experiments, the total main factor degrees of freedom, the F ratio at a 95% confidence, the significance level, the degrees-of-freedom of error, error variance, the effective number of replications and the number of replications for confirmation experiments, respectively [24,25]. The confidence interval was calculated as 1.554.…”
Section: Analysis Of Variance Results (Varyans Analizi Sonuçları)mentioning
confidence: 99%
“…The symbols N, Tdof, F α,1ƒe , α, ƒe, Ve, R and n eff represents the total number of experiments, the total main factor degrees of freedom, the F ratio at a 95% confidence, the significance level, the degrees-of-freedom of error, error variance, the effective number of replications and the number of replications for confirmation experiments, respectively [24,25]. The confidence interval was calculated as 1.554.…”
Section: Analysis Of Variance Results (Varyans Analizi Sonuçları)mentioning
confidence: 99%
“…This instrument had three current probes (CP-1201) and the measurements were made by connecting these probes separately to the energy input of the machine. In the study, since the effects of the cutting parameters on the power consumption were examined, it was reported that systems that increase the power consumption, such as the cooling system, should be turned off [78]. A schematic view of the turning experiments is presented in Figure 9.…”
Section: Resultsmentioning
confidence: 99%
“…Kesme hızının artması ile kesme kuvveti bileşenlerinin ve esas kesme kuvvetinin azalması kesme bölgesindeki ısının yükselmesi iş parçasının kayma dayanımının azalması ve takım/talaş ara yüzeyi temas alanının azalması ile açıklanabilir [26,30,31]. İlerleme miktarının artışına bağlı kesme kuvveti bileşenlerinin ve esas kesme kuvvetinin artması literatürde yaygın olarak karşılan bir durumdur [32][33][34].…”
Section: 1kesme Kuvveti Bileşenleriunclassified